DEVELOPING CHILDREN'S CHARACTER AND MOTOR SKILLS THROUGH SOCIALIZATION OF HANDBALL SPORTS IN LEBAKSONO VILLAGE - Riga Mardhika; Ramadhany Hananto Puriana; I Gede Dharma Utamayasa; Dwiki Chandra Hermawan; Achmad Ryan Yudha Ananta; End Ricko Ogestyan (Antis-publisher, 2026)
Objective: This community service activity was held as an effort to introduce handball sports to children while supporting the development of their character and motor skills. The background of the implementation of this activity is that there is still limited knowledge of the public, especially children, about handball sports and the need for physical activities that are able to stimulate the development of movement skills and the formation of positive character. Method: The methods used are in the form of a participatory approach through the delivery of materials, demonstrations of basic techniques, playing practices, and direct mentoring. The target of the activity is school-age children who live in Lebaksono Village. Evaluation was carried out using observation techniques during the implementation of activities and documentation as supporting data. Results: The results of the activity showed that participants experienced an increase in understanding of basic handball techniques, movement coordination skills, agility, and teamwork. In addition, participants also showed the development of discipline, responsibility, confidence, and sportsmanship during the entire series of activities. Thus, the socialization of handball sports can be used as one of the effective learning media in supporting the development of children's character and motor skills in the community. Novelty: The novelty of this community service activity lies in the use of handball sports socialization as an effective learning media in supporting the development of children's character and motor skills in the community.